3+6x=-4y

Simple and best practice solution for 3+6x=-4y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+6x=-4y equation:


Simplifying
3 + 6x = -4y

Solving
3 + 6x = -4y

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + 6x = -3 + -4y

Combine like terms: 3 + -3 = 0
0 + 6x = -3 + -4y
6x = -3 + -4y

Divide each side by '6'.
x = -0.5 + -0.6666666667y

Simplifying
x = -0.5 + -0.6666666667y

See similar equations:

| 7x^2-4x+.5717285714=0 | | -8r-4=7r-4 | | 8x^2+9x+6.5=0 | | x^2+3.81x+3.61=0 | | 2.5d=40+50 | | .2(d-6)=.3d+5-3+.1d | | x^2+2.40x+1.44=0 | | 4x+5=x+32 | | 57.86-9.95= | | 18k^3-48k^2+66k= | | 2.5d=0.4+50 | | -10x^3+5x^2+140= | | 300.000-24.677= | | 5+4d=-13-2d | | (2x+8)=(7x-1) | | 38.700-11.865= | | 3b-6=-b-2 | | (-3x^7)(6x^8)= | | 14.080-9.199= | | (3x-3)+(6x-6)=90 | | 2(m-30)=-6m | | 78.110-45.876= | | Y=4-3(0) | | w^2+8w+25=0 | | 16n^2-56n=-47 | | -2+0.5n=-5 | | 6+2x=6(18+6x) | | 12x+5x^2-9x^3=0 | | x^3-36x^2+72x-168=0 | | .25+14=38 | | (3x^4+3x^3-8)-(2x^2-9x+7)= | | -8k-5=2k+15 |

Equations solver categories